2002
DOI: 10.1029/2001jd000850
|View full text |Cite
|
Sign up to set email alerts
|

On the changing nature of the regional connection between the North Atlantic Oscillation and sea surface temperature

Abstract: Evidence is presented that the correlation between the North Atlantic Oscillation (NAO), in terms of the NAO index, and the North Atlantic sea surface temperature (SST) is not stationary. This is inferred from both reanalysis data from the U.S. National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) and the Kaplan sea surface temperature data set. Two phases of winterly North Atlantic atmosphere‐ocean covariability are identified by means of linear regression and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 50 publications
6
61
0
3
Order By: Relevance
“…He suggested that year-toyear SST fluctuations arise from heat fluxes at the atmosphere-ocean interface; on longer timescales, the changes in the ocean circulation play a primary role in SST variability. The conclusions of Bjerknes (1964) were confirmed by many later studies (Cayan, 1992a(Cayan, , 1992bDeser and Blackmon, 1993;Kushnir, 1994;Halliwell, 1998;Walter and Graf, 2002;Wu and Gordon, 2002).…”
Section: Nao and Ocean Temperature Variabilitysupporting
confidence: 72%
See 2 more Smart Citations
“…He suggested that year-toyear SST fluctuations arise from heat fluxes at the atmosphere-ocean interface; on longer timescales, the changes in the ocean circulation play a primary role in SST variability. The conclusions of Bjerknes (1964) were confirmed by many later studies (Cayan, 1992a(Cayan, , 1992bDeser and Blackmon, 1993;Kushnir, 1994;Halliwell, 1998;Walter and Graf, 2002;Wu and Gordon, 2002).…”
Section: Nao and Ocean Temperature Variabilitysupporting
confidence: 72%
“…Simulated regional surface air temperature and precipitation patterns are in agreement with large-scale patterns typical for the positive NAO trend (Hurrell, 1995;Thompson and Wallace, 2001). Previously reported analyses of the North Atlantic SST (Cayan, 1992a(Cayan, , 1992bDeser and Blackmon, 1993;Kushnir, 1994;Dickson et al, 1996;Grötzner et al, 1998;Delworth and Greatbatch, 2000;Curry and McCartney, 2001;Walter and Graf, 2002;Brauch and Gerdes, 2005) have shown that on interannual timescales the ocean surface over the North Atlantic is strongly influenced by the NAO, especially in the winter. In fact, the ocean surface temperature and salinity anomalies develop as a time-integrated response to persistent NAO air-sea heat and freshwater flux anomalies.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The covariability of the tripole SST pattern and the NAO has been shown to vary on multidecadal time scales by Walter and Graf (2002). Their correlation weakens from the 1930s to the early 1960s, and increases during the last decades of the century.…”
Section: A Observed Sst 1870-2004mentioning
confidence: 99%
“…Their correlation weakens from the 1930s to the early 1960s, and increases during the last decades of the century. As noted by Walter and Graf (2002), these periods correspond respectively to a warm and a cold phase of the multidecadal variability. During the latter, the NAO was characterized by enhanced variability on the quasidecadal time scale, matching the amplitude modulation of the quasi-decadal SST oscillation in Fig.…”
Section: A Observed Sst 1870-2004mentioning
confidence: 99%